UPPER-MANTLE REFLECTORS: MODELLING OF SEISMIC WAVEFIELD CHARACTERISTICS AND TECTONIC IMPLICATIONS - Hansen T.M.; Balling N. (My University, 2004)
Deep seismic experiments on continental lithosphere generally reveal marked reflectivity from structures in the crust and a significant decrease in reflectivity from the upper mantle. However, reflected and refracted energy from mantle lithosphere are observed in both near-normal incidence and wide-angle data. The origin of the reflective structures is a matter of debate. Hypotheses include remnant subduction zones, shear zones, fluids and seismic anisotropy. Through analytical and numerical modelling studies, including full wavefield modelling, we investigate seismic characteristic signatures generated from a variety of geologically plausible models. We have found that both upper-mantle shear zones of reduced velocity and density and remnant subduction slabs containing high-density eclogites may contain sufficient seismic impedance contrasts to normal mantle peridotites to generate near-normal incidence reflectivity. Wide-angle energy originates from subduction slabs containing either high- or lowvelocity eclogites, whereas intermediate-velocity eclogites are unlikely to produce significant wide-angle phases. In general, energy of seismic phases originating from upper-mantle zones of anomalous seismic velocities and densities is significantly increased if homogeneous zones are replaced by zones of inhomogeneous petrophysical properties resulting from constructive interference. Maximum wavefield anomalies are generated from sub Moho dipping slabs of incomplete transformation of low-velocity/low-density crustal material to high-velocity/highdensity eclogites. Localized shear zones generated in mantle peridotite generally do not produce significant wide-angle energy. Only if highly inhomogeneous structures containing material of marked (ca 10 per cent) velocity and density reduction are present, may shear zones be observed in wide-angle data. Analyses of two specific deep-seismic data sets (MONA LISA data) from the North Sea and (BABEL data) from the Baltic Sea, show good agreement between observations and modelling results for dipping remnant subduction slabs containing small-scale inhomogeneities associated with incomplete transformation. Our modelling results improve our possibilities of distinguishing between two often contrasting tectonic interpretations for dipping upper-mantle seismic reflectors, the remnant subduction and shear zone models.
Keywords: eclogite; reflection seismology; refraction seismology; remnant subduction; shear zones; upper mantle